Management Anesthesia of Esophagostomy in a Patient with a Double Outlet Right Ventricle - Bimo Kusumo Bhirowo; Rudy Vitraludyono (Faculty of Medicine, Brawijaya University, 2021)
Background: Esophageal atresia is a congenital disorder in which there is no esophagus because the proximal and distal esophagus is not connected. Babies with esophageal atresia can show several symptoms: foamy mouth, cyanosis, coughing and tightness, flatulence, oliguria, or worse, pneumonia symptoms. Accompanying anomalies occur in greater than 50% of neonates with esophageal atresia. Esophageal atresia is identified by ultrasound at 18 weeks of gestation, ultrasound, and Magnetic resonance imaging (MRI) of the fetal neck, or examination of a nasogastric tube in the neck of a newborn. The management of esophageal atresia is challenging. The main choice remains the surgical procedure, which usually involves making a stoma on the proximal esophagus and gastrostomy. However, surgery has risky complications.Case: In this case, it was reported that a 22-day-old baby with tracheoesophageal fistula (TEF) type C with Ventricular Septum Defect and Atrial Septum Defect and Double Outlet Right Ventricle (DORV) underwent esophagostomy surgery with general anesthesia.Conclusion: Anesthesia management with general anesthesia, intubation using intravenous ketamine 3 mg, fentanyl 3µg, atracurium 1.5 mg gives stability for esophagostomy in a patient with a double outlet right ventricle.